"Петрушка" Фокіна-Стравінського-Бенуа - три рівні прояву художніх новацій першого десятиліття ХХ століття - Косаковська, Леся Петрівна; Kosakovska, Lesia P. (Національна академія керівних кадрів культури і мистецтва, 2013)
У статті досліджено сутність художніх особливостей класичного танцю та культурного середовища початку XX століття. На прикладі створення балету "Петрушка" зроблено узагальнюючі висновки про органічну єдність хореографії М. Фокіна, музики І. Стравінського і театрального живопису О. Бенуа як складових новаторського балетного спектаклю. The article examines Russian choreography of early twentieth century. Defined regularities and results of creativity search of essence of artistic features and significant tools of classical dance in the context of the cultural environment of that period on the example of ballet "Petrushka" by Fokine - Stravinsky - Benois. M. Fokine justly believed that ballet "Petrushka" can be described as a dramatic piece of music of Stravinsky, which occupies an exceptional position among new music. Music for "Petrushka" was the first herald of a "new life". And Stravinsky didn't stop create, because he started think differently. He gave up on admiring people's poetic fantasy, romance, poetic contemplation and imitation. Life, straggle, love, movement, games and dances become active force. Intensity and softness of expression perform forward to change mental architectonics. The revolution in Stravinsky's thinking manifested primarily in the fact that he didn't feet the form as completely self-sufficient scheme which pressure on the mind. On the contrary, music thought creates form.
"Petrushka" by Stravinsky, Fokine, Benois - three levels of manifestation of artistic innovations of the first decade of the twentieth century
Keywords: балетмейстер; choreographer; класичний танець; classic dance; Russian ballet; dance image; composer; score; theatrical painting; dance theater; російський балет; хореографічний образ; композитор; партитура; театральний живопис; хореографічний театр